Outcomes Pre-Intermediate: Workbook - Nuttall C.; Evans David (Andover National Geographic Learning, Cengage Learning, 2016)
The second edition of Outcomes has been fully revised and updated to provide contemporary, global content and stunning National Geographic photos and videos. its trademark lexically-rich approach shows students how vocabulary works, and the evenly paced grammar syllabus provides examples and tasks based on what people actually say and write. With a huge variety of talking points and practice, Outcomes teaches students the English they need to communicate outside the classroom.
Keywords: 811.111